Efektivitas Manajemen Pengawasan Dalam Proses Bantuan Dana Hibah - Muhammad Iqbal Nasution; Annio Indah Lestari Nasution (Universitas Labuhanbatu, 2022)
This journal aims to determine how effective if the time used is shortened in the flow of the proposal file submission process up to the stage of disbursement of grant funds but does not reduce the effectiveness of the previous. This research uses the method (Research & Development) or research development which focuses on the purpose of developing, expanding, and digging further on a theory in a particular discipline. The results of the discussion said that in the process of Grant Assistance can not be done quickly because it must be done carefully as possible.